Different Life Cycle Stages of Plasmodium falciparum Induce Contrasting Responses in Dendritic Cells - Yap, Xi Zen; Lundie, Rachel J.; Feng, Gaoqian; Pooley, Joanne; Beeson, James G.; O'Keeffe, Meredith (Frontiers in Immunology, 2019)
Dendritic cells are key linkers of innate and adaptive immunity. Efficient dendritic cell activation is central to the acquisition of immunity and the efficacy of vaccines. Understanding how dendritic cells are affected by Plasmodium falciparum blood-stage parasites will help to understand how immunity is acquired and maintained, and how vaccine responses may be impacted by malaria infection or exposure. This study investigates the response of dendritic cells to two different life stages of the malaria parasite, parasitized red blood cells and merozoites, using a murine model. We demonstrate that the dendritic cell responses to merozoites are robust whereas dendritic cell activation, particularly CD40 and pro-inflammatory cytokine expression, is compromised in the presence of freshly isolated parasitized red blood cells. The mechanism of dendritic cell suppression by parasitized red blood cells is host red cell membrane-independent. Furthermore, we show that cryopreserved parasitized red blood cells have a substantially reduced capacity for dendritic cell activation.